Working the Stroll: Prostitutes, Pimps, and Johns. Issue 12 (1st December 2016) - McCutcheon, James C.; Mustaine, Elizabeth Ehrhardt; Tewksbury, Richard
ABSTRACT: Prostitution is one of the most publicly recognized crimes, yet one which we have limited information. Particularly, we have little knowledge of male prostitution and not much information on the locations of sexual transactions. This study fills a void in the research as we apply journey to crime theory to the question of "where" as it applies to male prostitution. Data gathered from Chicago calculate the distance traveled and arrest location for the purchase and trade of sexual services. Findings demonstrate johns travel the greatest distance from their home addresses to the arrest location, followed by pimps, then prostitutes.